Regular in-situ simulation training of paediatric Medical Emergency Team leads to sustained improvements in hospital response to deteriorating patients, improved outcomes in intensive care and financial savings. (June 2017) - Theilen, Ulf; Fraser, Laura; Jones, Patricia; Leonard, Paul; Simpson, Dave
Abstract: Aim of the study: The introduction of a paediatric Medical Emergency Team (pMET) was accompanied by weekly in-situ simulation team training. Key ward staff participated in team training, focusing on recognition of the deteriorating child, teamwork and early involvement of senior staff. Following an earlier study [1], this investigation aimed to evaluate the long-term impact of ongoing regular team training on hospital response to deteriorating ward patients, patient outcome and financial implications. Methods: Prospective cohort study of all deteriorating in-patients in a tertiary paediatric hospital requiring admission to paediatric intensive care (PICU) the year before, 1 year after and 3 years after the introduction of pMET and team training. Results: Deteriorating patients were recognised more promptly (before/1 year after/3years after pMET; median time 4/1.5/0.5 h, p < 0.001), more often reviewed by consultants (45%/76%/81%, p < 0.001) and more rapidly escalated to PICU (median time 10.5/5/3.5 h, p = 0.02). There was a significant reduction in associated PICU admissions (56/51/32, p = 0.02) and PICU bed days (527/336/193, p < 0.001). The total annual cost of training (£74, 250) was more than offset by savings from reduced PICU bed days (£801, 600 per annum). Introduction of pMET coincided with significantly reduced hospital mortality (p < 0.001). Conclusion: These results indicate that lessons learnt by ward staff during team training led to sustained improvements in the hospital response to critically deteriorating in-patients, significantly improved patient outcomes and substantial savings. Integration of regular in-situ simulation training of medical emergency teams, including key ward staff, in routine clinical care has potential application in all acute specialties.